An Extension of the Compression-expansion Fixed Point Theorem of Functional Type - Himanshu Tiwari; Subhashish Biswas (International Journal of Mathematics And its Applications, 2020)
In this article we use an interval of functional type as the underlying set in our compression-expansion fixed point theorem argument which can be used to exploit properties of the operator to improve conditions that will guarantee the existence of a fixed point in applications. An example is provided to demonstrate how intervals of functional type can improve conditions in applications to boundary value problems. We also show how one can use suitable k-contractive conditions to prove that a fixed point in a functional-type interval is unique.